The Level of Knowledge of Futsal Extracurricular Students at SMPN 11 Banjarbaru on Tactics and Strategies in Futsal Sports - Fernando, Calvin; Arifin, Ramadhan; Amirudin, Akhmad (Empiricism Journal, 2026)
This study aimed to analyze the level of knowledge of tactics and strategies among students participating in futsal extracurricular activities at SMPN 11 Banjarbaru. Understanding tactical and strategic concepts is essential because these aspects influence players’ decision-making, positional awareness, and team performance during matches. This study employed a quantitative descriptive method with a survey approach. The population consisted of 42 students who participated in futsal extracurricular activities, and 15 students were selected as samples using purposive sampling based on active participation criteria. The research instrument was a questionnaire consisting of 47 true-false statements adapted from previous research, with a reliability coefficient of 0.982. The data were analyzed using descriptive percentage analysis. The results showed that one student was in the very low category, three students were in the low category, eight students were in the medium category, one student was in the high category, and two students were in the very high category. Overall, the level of knowledge of futsal tactics and strategies among students at SMPN 11 Banjarbaru was categorized as medium. These findings indicate that students have a basic understanding of futsal tactics and strategies, but their knowledge still needs to be strengthened through more structured, varied, and contextual training programs. The results of this study can serve as evaluation material for coaches and schools in improving the quality of futsal extracurricular coaching.